(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Since the 1950s the teaching of the Russian language in Chinese universities experienced a long period of decline. Despite some improvements in the 1990s, the reality that Russian turned from a “great and mighty” into a “small” language still exists today. With the onset of the 21st century, against the background of the constant strengthening of Chinese-Russian relations and, in particular, the establishment of a Chinese-Russian strategic partnership, the demand for Russian-speaking specialists is growing every day. This demand is further stimulated by the launch and steady implementation of the One Belt, One Road initiative. If we talk about students of natural science and technical universities, the study of the Russian language expands their professional horizons, increases and enriches their knowledge in advanced specialized areas. Due to historical reasons, there are quite a few students who speak both the specialty and the Russian language today. In our university, the subject of the Russian language is included in the compulsory curriculum for students of natural sciences and technical disciplines. Based on the current state of Russian language teaching in our university, in this article we consider the need to reform the Russian language curriculum in higher education institutions from different points of view.